História, nação e raça no contexto da exposição do centenário em 1922 (2014)
The subjects addressed in this article are the public and academic debates about the history of Brazil that took place in the context of the Centennial Exhibition held in 1922 in the city of Rio de Janeiro. The aim is to highlight how certain concepts of nation and race were debated in academic discussions about history, anthropology and archaeology, how they were related to the nation’s history, and how they ultimately became a part of the nation’s self-image. Furthermore, the article investigates how and by whom these ideals were contested.